Case Report: Hexachloroethane Smoke Inhalation: A Rare Cause of Severe Hepatic Injuries - Loh, Ching-Hui (National Institute of Environmental Health Sciences, 2006)
CONTEXT: We report on two patients, a 23-year-old man and a 24-year-old man, who had chemical pneumonitis and respiratory distress after inhaling hexachloroethane/zinc oxide (HC/ZnO) smoke during military training. CASE PRESENTATION: The patients had been healthy previously and denied any history of alcohol or drug abuse. Hematologic tests revealed leukocytosis with neutrophils predominant. The respiratory conditions of both patients improved after steroid therapy and oxygen support, but deterioration of liver function was found. The laboratory results showed that alanine aminotransferase (ALT) and γ-glutamyl transpeptidase levels were elevated about 1.5-fold the normal limits and that aspartate aminotransferase (AST) levels were marginally elevated. The elevation of liver aminotransferase started from day 1 and day 2 and peaked from day 18 to day 22. ALT/AST levels then returned to normal in 6 weeks. Common viral hepatitis was ruled out after serologic tests. Abdominal sonography and physical examination failed to show any specific findings. DISCUSSION: The hepatotoxic effect was attributed to inhalation of high-concentration HC/ZnO smoke in an enclosed area, where several hepatotoxicants, including ZnCl(2), HC, and chlorinated vapors, could have been generated and mixed in the smoke. RELEVANCE TO CLINICAL PRACTICE: These case reports elaborate the hepatic effects that may occur in addition to pulmonary effects of HC/ZnO smoke.